Fast Measurement Method for Worm Profile by Line Laser Displacement Sensor - Jianzhou Pan; Aiping Song; Chuang Yan; Ning Mei (Jixie chuandong, 2021)
A line laser non-contact measurement method which can detect the worm profile quickly and reliably is proposed. The worm comprehensive deviation detection platform is constructed mainly based on the line laser displacement sensor， which can quickly and accurately collect and analyze the data of the worm profile. At the same time， the real three-dimensional model and equation expression of the measured worm are constructed based on the least square method， by comparing with the theoretical model of worm， the geometric dimension deviation data of worm can be obtained. This method is fast and efficient， and the deviation data is accurate and reliable.